Off-label prescribing of antipsychotics - a questionnaire survey of Finnish physicians - Pentinlehto Jami; Haapea Marianne; Ylitolonen Lotta; Alakokkare Anni-Emilia; Niemelä Solja; Miettunen Jouko; Penttilä Matti; Koponen Hannu; Seppälä Jussi; Isohanni Matti; Rautio Nina; Jääskeläinen Erika (Psykiatrian Tutkimussäätiö, 2022)
Antipsychotics (APs), especially second-generation antipsychotics, are being increasingly used around the world. At the same time their off-label use has also increased worldwide, as well as in Finland. The aim of our study was to find out the off-label prescribing of APs in Finland among physicians in different healthcare units. Antipsychotics (APs), especially second-generation antipsychotics, are being increasingly used around the world. At the same time their off-label use has also increased worldwide, as well as in Finland. The aim of our study was to find out the off-label prescribing of APs in Finland among physicians in different healthcare units. The study was conducted as a questionnaire survey. Particular attention was paid to practices between psychiatrists and other physicians (mostly general practitioners and occupational health doctors). Similar studies have not been conducted on this topic in Finland before. Altogether 216 physicians answered the questionnaire. The most common indications for off-label prescription were insomnia and anxiety, and this was evident for both psychiatrists as well as other physicians. Quetiapine was the one most commonly prescribed off-label AP. Over one-third of psychiatrists (39%) and about one-third of other physicians (30%) did not give instructions on the length of the treatment. The metabolic values were reported to be followed by 44% of the psychiatrists and by 18% of other physicians. Nearly two-thirds of all respondents thought that off-label use had more benefits than harms. Compared to other physicians, psychiatrists prescribed APs for off-label use more frequently and for more varied psychiatric conditions. Off-label use of APs seems to be a clinical reality in Finland. There is need for further studies on efficacy and adverse effects of APs in off-label use, and also a need for clinical guidelines on monitoring the patients using APs off-label.